Pengaruh Kemiskinan Terhadap Tingkat Pendidikan Generasi Penerus Keluarga Di Kecamatan Rangsang Barat Kabupaten Kepulauan Meranti - Putri, Desy Try Anandika; Syahza, Almasdi; Asmit, Brilliant (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research is a type of quantitative method research that aims to determine the effect of poverty on the level of education of the next generation of families in West Rangsang District, Meranti Islands Regency. This study took variables consisting of independent variables, namely poverty, and the dependent variable, namely the level of education. The data collection techniques used were documentation and questionnaires. Based on the results of the research that has been conducted, it shows that poverty affects the level of education of the next generation of families by using a simple linear regression formula and hypothesis testing using the t (partial) test. The research findings show that the low level of education, especially in the Meranti Islands Regency area where the poverty rate is high. So that it causes obstacles in access to education and reduces the quality of human resources. Therefore, efforts to improve education in rural areas through economic empowerment and the role of government policies are very important to reduce poverty and encourage social progress.